THE NATURE OF METASOMATISM IN THE SUB-ARC MANTLE WEDGE: EVIDENCE FROM RE-OS ISOTOPES IN KAMCHATKA PERIDOTITE XENOLITHS - Widom E.; Kepezhinskas P.; Defant M. (My University, 2003)
We have performed Re–Os isotope measurements on a suite of 21 Kamchatka mantle xenoliths including 19 harzburgites and two lherzolites, from the northern arc front (Valovayam Volcano), the southern arc front (Avachinsky Volcano), and behind the arc front in the south (Bakening Volcano). Os and Re concentrations vary from 0.02 to 8.2 and 0.003 to 0.437 ppb, respectively, and 187Re/188Os varies from 0.004 to 3.811. 187Os/188Os ratios range from 0.1226 to 0.1566. Regional variations in Re–Os isotope signatures are apparent, with peridotites from Avachinsky exhibiting the least radiogenic Os isotope signatures and lowest Re/Os ratios, and those from Bakening the most radiogenic Os and highest Re/Os. Peridotites from Valovayam span the distinct compositional fields defined by the Avachinsky and Bakening peridotites. All of the Kamchatka peridotites are, however, characterized by radiogenic 187Os/188Os compared to non-arc continental peridotites with comparable Re abundances or Re/Os ratios.